Mechanism of Intramolecular Photostabilization in Self‐Healing Cyanine Fluorophores. Issue 18 (2nd December 2013) - van der Velde, Jasper H. M.; Ploetz, Evelyn; Hiermaier, Matthias; Oelerich, Jens; de Vries, Jan Willem; Roelfes, Gerard; Cordes, Thorben
Abstract Organic fluorophores, which are popular labels for microscopy applications, intrinsically suffer from transient and irreversible excursions to dark‐states. An alternative to adding photostabilizers at high concentrations to the imaging buffer relies on the direct linkage to the fluorophore. However, the working principles of this approach are not yet fully understood. In this contribution, we investigate the mechanism of intramolecular photostabilization in self‐healing cyanines, in which photodamage is automatically repaired. Experimental evidence is provided to demonstrate that a single photostabilizer, that is, the vitamin E derivative Trolox, efficiently heals the cyanine fluorophore Cy5 in the absence of any photostabilizers in solution. A plausible mechanism is that Trolox interacts with the fluorophore through intramolecular quenching of triplet‐related dark‐states, which is a mechanism that appears to be common for both triplet‐state quenchers (cyclooctatetraene) and redox‐active compounds (Trolox, ascorbic acid, methylviologen). Additionally, the influence of solution‐additives, such as cysteamine and procatechuic acid, on the self‐healing process are studied. The results suggest the potential applicability of self‐healing fluorophores in stochastic optical reconstruction microscopy (STORM) with optical super‐resolution. The presented data contributes to an improved understanding of the mechanism involved in intramolecular photostabilization and has high relevance for the future development of self‐healing fluorophores, including their applications in various research fields.